The Effect of Financial Knowledge, Financial Attitude, and Lifestyle Pattern on Financial Management Behavior with Locus of Control as a Mediating Variable - Pujianti, Lailatunnisa; Umaimah, Umaimah (JURNAL ONLINE INSAN AKUNTAN, 2024)
Financial management behavior is something that must be understood today. Many people with sufficient income levels often still face financial behavior problems. financial management behavior is influenced by several factors which are financial knowledge, financial attitude, lifestyle patterns, and locus of control. In analyzing it, this research uses quantitative methods to evaluate the object of Generation Z accountants in the Gresik area and data collection is carried out through distributing online questionnaires using a Likert scale. Through various test processes, the results show that Financial Knowledge and Lifestyle Pattern have no significant effect on Locus of Control. However, Financial Attitude has a highly significant effect on Locus of Control, emphasizing the role of attitudes towards money in shaping individual control over financial events. When it comes to financial behavior, Financial Knowledge and Lifestyle Pattern have no significant effect, while Financial Attitude and Locus of Control have a significant impact. In the context of mediation, only Financial Attitude is able to mediate the relationship between Locus of Control and Financial Management Behavior, while Financial Knowledge and Lifestyle Pattern have no mediating effect.